2007
DOI: 10.1098/rsbl.2007.0234
|View full text |Cite
|
Sign up to set email alerts
|

Female preferences drive the evolution of mimetic accuracy in male sexual displays

Abstract: Males in many bird species mimic the vocalizations of other species during sexual displays, but the evolutionary and functional significance of interspecific vocal mimicry is unclear. Here we use spectrographic cross-correlation to compare mimetic calls produced by male satin bowerbirds (Ptilonorhynchus violaceus) in courtship with calls from several model species. We show that the accuracy of vocal mimicry and the number of model species mimicked are both independently related to male mating success. Multivar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 11 publications
1
45
0
5
Order By: Relevance
“…These coefficients reflect the similarity between two sounds and range from zero, when there is no similarity, to one, when the sounds are identical (Clark et al 1987; Coleman et al 2007). The effects of background noise on our results were minimized by computing the SPCC coefficients using only the frequency bands covered by each syllable type.…”
Section: Methodsmentioning
confidence: 99%
“…These coefficients reflect the similarity between two sounds and range from zero, when there is no similarity, to one, when the sounds are identical (Clark et al 1987; Coleman et al 2007). The effects of background noise on our results were minimized by computing the SPCC coefficients using only the frequency bands covered by each syllable type.…”
Section: Methodsmentioning
confidence: 99%
“…Species vary in the bower traits favouring mating success, which may include the number of coloured decorations [11], avenue form [12] or bower paint [13,14]. Females may also choose mates based on physical traits such as vocal mimicry [15] and courtship movements [16]. Different components of male displays may serve different functions; for example, the white bones at the entrance of male spotted bowerbird (Ptilonorhynchus maculatus) bowers may attract females to the bower, while glass objects may stimulate the female once in the bower [17].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Okida et al (2010) showed a significant e#ect of vocalisation during the display on the mating success in this species. Recent studies on the bower display showed that various characteristics of display a#ected the male mating success, including the quality of the bower structure (Borgia 1985b), decorations (Borgia 1985b, Madden 2003a, 2003b), male's painting behaviour , vocal mimicry (Lo#redo & Borgia 1986, Coleman et al 2007, and intensity of behavioural display (Patricelli et al 2002, Coleman et al 2004. Thus, the bower display is composed of multiple sexual signals.…”
Section: Multiple Components Of Displaymentioning
confidence: 99%